SISTEM INFORMASI PENDATAAN PENDUDUK DESA DETUSOKO BARAT KECAMATAN DETUSOKO KABUPATEN ENDE BERBASIS WEB - Grasiana Oliva Londa; Ferdinandus Lidang Witi; Benediktus Yoseph Bhae (Pusat Riset dan Inovasi Nasional, 2022)
The village office of West Detusoko is one of the government agencies that serves the community directly in collecting data on the occupation. Population data collection in the village of West Detusoko currently uses computerization, namely using Microsoft Word and Microsoft Excel application programs. but there are still many errors and the possibility of data loss, input errors, doubling of data input and the difficulty of searching for population data so that it takes a long time and causes delays in making reports. The purpose of this study is to build a population data collection information system using language PHP programming and database In this study the author uses a qualitative descriptive approach. The software design method used is the waterfall method. The testing method used by the author is blackbox testing. With this information system, it can help overcome the problems of population data collection in West Detusoko Village.